Health and Well-Being in the Workplace: A Review and Synthesis of the Literature - Danna, Karen; Griffin, Ricky W. (Journal of Management, 1999)
Health and well-being in the workplace have become common topics in the mainstream media, in practitioner-oriented magazines and journals and, increasingly, in scholarly research journals. In this article, we first review the literature that serves to define health and well-being. We then discuss the primary factors associated with health and well-being, the consequences of low levels of health and well-being, and common methods for improving health and well-being in the workplace. Finally, we highlight important future directions for future theory, research, and practice regarding health and well-being from an organizational perspective.